KINETICSOF VULCANISATION IN NATURAL RUBBER IN THE PRESENCE OF NITROSAMINE-FREE ACCELERATORS - Arunashanthi, K.D. (My University, 2016)
Attached

Much attention has focused on nitrosamines in the rubber industry-both in workplace air and in the rubber products themselves. Thus while a correlation between accelerator usage and nitrosamine formation is well known, the efficiency of such conversion appears to be highly variable. Since nitrosamines are derivatives of secondary amines, as are many rubber chemicals (accelerators and sulphur donors) a correlation between accelerator usage and nitrosamine formation is not surprising, the link having been established as long ago as 1980. The proposed work will involve a detailed investigation of the way in which Nitrosamine-free accelerators influence the Kinetics of cross-linking in natural elastomers.